Overview of knowlegde, attitude and practice about breakfast among students in faculty of medicine and health sciences of Krida Wacana Christian University in 2020 - Christin Kaiwai; Gracia JMT Winaktu; Bhanu Bhanu; Luciana Budiati Sutanto (Indonesian Nutrition Association, 2022)
Breakfast is beneficial for maintaining concentration, mental health, and improving cognitive function. Students are expected to have knowledge, attitude and good behavior regarding breakfast. This study aims to obtain an overview of knowledge, attitudes and behaviors about breakfast among students in Faculty of Medicine and Health Sciences of Krida Wacana Christian University, in 2020.